Study of Effectiveness of the Argument-driven Inquiry Pedagogy in Science Classrooms of India - Mukherjee, Anirban; Bhowmick, Plaban Kumar; Khan, Saddam; Ghosh, Chinmoy Kumar (SCHOOL SCIENCE, 2020)
Implementation of Argument-driven Inquiry (ADI) pedagogy in India would face many impediments due to the detrimental alliance of the curricula with its transaction time, infrastructural limitations, and the evaluation system. The teaching learning system with the sole aim of securing high marks is more prone to rote learning. Hence, we attempted to modify the ADI according to the Indian context, and try out the pedagogy for science classrooms in Indian schools. For this purpose, studies were conducted in the form of workshops for both Physical and Biological Sciences in schools of rural and urban sectors. We have narrated the experiences gathered from the Biological Science workshops in the form of a first-hand case study in this paper. It has been observed from the studies that notwithstanding the impediments, this pedagogy can be very useful for the teachers and the all-important students if it can be judiciously amalgamated with the ongoing teaching strategies within the constraints of time, space and infrastructure